Role of p35/Cdk5 in preplate splitting in the developing cerebral cortex. - Rakić, S; Davis, C; Molnár, Z; Nikolić, M; Parnavelas, J (2006)
The earliest generated cells of the mammalian cerebral cortex form the preplate layer (PPL). The subsequently born cortical plate (CP) cells split this layer into the superficial layer I (LI) and the deep subplate (SP). The cellular and molecular mechanisms that underlie this event are unclear. To investigate the role of the cyclin-dependent kinase 5 (Cdk5) and its activator p35 in preplate splitting, we used Nissl staining, carbocyanine dye tracing, cell birthdating, and immunohistochemistry for calretinin (CalR) in p35 and Cdk5 knockout mice. Our data demonstrated changes in early cortical lamination and aberrant thalamic axon trajectories in these mice. Specifically, LI was thicker, and cell-dense and thalamic axons did not accumulate in the SP layer before invading the CP. Instead, they grew past the SP and more superficial cortical layers and coursed obliquely toward the pial surface. This behavior has been previously observed in reeler mice and suggests a defect in PPL splitting. CalR immunohistochemistry and bromo-deoxyuridine birthdating confirmed the abnormality in position of the earliest generated cortical cells of mutants. These observations suggest that the p35/Cdk5 pathway plays a role in preplate splitting in addition to regulating layer formation.